2020
DOI: 10.1186/s43042-020-00080-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of swimming on muscle PGC-1α, FNDC5 mRNA, and assessment of serum omentin, adropin, and irisin in high carbohydrate high fat (HCHF) diet induced obesity in rats

Abstract: Background Exercise benefits a variety of organ systems in mammals, and some of the best recognized effects of exercise on muscle are mediated by the transcriptional peroxisome proliferator-activated receptor gamma co-activator 1-α (PGC-1α). The regulatory effect of swimming on muscle PGC-1α, FNDC5 mRNA expression, and subsequently irisin levels is more controversial. This study aimed to investigate the role of swimming as an exercise on the expression of peroxisome proliferator-activated receptor-gamma coacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The increase in PGC-1α after exercise stimulates a growth in FNDC-5 protein, which cleavages to form irisin [54], activating the UCP-1 thermogenic gene to enhance thermogenesis [14]. Previous studies also reported higher PGC-1α in experimental mice after swimming treatment than in the control group [55]. The same results have been reported on the mouse model after 30 minutes of treadmill exercise [53].…”
Section: Resultssupporting
confidence: 67%
“…The increase in PGC-1α after exercise stimulates a growth in FNDC-5 protein, which cleavages to form irisin [54], activating the UCP-1 thermogenic gene to enhance thermogenesis [14]. Previous studies also reported higher PGC-1α in experimental mice after swimming treatment than in the control group [55]. The same results have been reported on the mouse model after 30 minutes of treadmill exercise [53].…”
Section: Resultssupporting
confidence: 67%
“…The mechanism of the beneficial effects of adropin on the endothelial function has shown that serum adropin promotes production and improves the bioavailability of nitric oxide, which improves arterial stiffness. These results indicated that serum adropin has a possible mechanism that underlies enhanced endothelial function (Badawy et al, 2020).…”
Section: Ldlmentioning
confidence: 77%
“…Symptoms of metabolic syndrome such as hypertension, dyslipidemia, impaired glucose tolerance, excess fat deposition, increased proinflammatory markers, and reduced antioxidant defenses were caused by highcarbohydrate, high-fat diet (HCHFD) in rats (Badawy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Irisin hormone has a vital role in obesity and is described as a myokine that induces white fat “browning” and thermogenesis stimulating UCP1 expression( 40 ). Swimming as an example of exercise elevated irisin levels and UCP1 expression provoking white adipocytes browning alleviating obesity( 41 ). In the present study, HFD reduced thermogenesis as evidenced by decreased levels of irisin, UCP1, and CD137 expressions (beige adipocyte markers).…”
Section: Discussionmentioning
confidence: 99%